PENGARUH KOMPETENSI PAEDAGOGIK TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI MA SEJAHTERA - Azhari Nur Alam (Fakultas Agama Islam Universitas Islam Jakarta, 2023)
Competency is a set of knowledge, skills, behavior and intelligent actions that must be possessed, internalized and controlled by teachers or lecturers with full responsibility in carrying out professional duties to achieve the required goals in accordance with the expected conditions. In short, pedagogical competence is the teacher's ability to manage learning. Motivation is a series of efforts to provide certain conditions so that someone wants and wants to do something. This research method uses the descriptive analytic correlation method. The data collection techniques used were observation, interviews, questionnaires. This research aims to determine whether there is an influence of pedagogical competence on students' learning motivation at MA Sejahtera. The method used in this research is correlation with a quantitative approach, the sampling method is carried out using Simple Random Sampling, with a total of 30 students as respondents.